(untitled) (Revista de Estudos da Linguagem, 2002)
In retrospect, perhaps the deepest issue in the evolution of textlinguistics was whether the concept of the ‘text’ would be adaptedand restricted to fit the conventional linguistics of the sentence, orwhether it would lead to a novel conception of linguistics itself.The second alternative has evidently won out through theestablishment of the text as a communicative event rather thanmerely a linguistic unit. A fundamental shift of perspective hasensued from formalism toward functionalism, raising the prospectof redesignating the field as a ‘text science’ that restores languageand text to the broader contexts of communication both withinscience and about science.